Functional and molecular genetic analyses of nine newly identified XPD‐deficient patients reveal a novel mutation resulting in TTD as well as in XP/CS complex phenotypes. Issue 7 (25th June 2013) - Schäfer, Annika; Gratchev, Alexei; Seebode, Christina; Hofmann, Lars; Schubert, Steffen; Laspe, Petra; Apel, Antje; Ohlenbusch, Andreas; Tzvetkov, Mladen; Weishaupt, Carsten; Oji, Vinzenz; Schön, Michael P.; et al.
Abstract The xeroderma pigmentosum (XP) group D protein is involved in nucleotide excision repair (NER) as well as in basal transcription. Determined by the type of XPD mutation, six different clinical entities have been distinguished: XP, XP with neurological symptoms, trichothiodystrophy (TTD), XP⁄TTD complex, XP⁄Cockayne syndrome (CS) complex or the cerebro‐oculo‐facio‐skeletal syndrome (COFS). We identified nine new XPD‐deficient patients. Their fibroblasts showed reduced post‐UV cell survival, reduced NER capacity, normal XPD mRNA expression and partly reduced XPD protein expression. Six patients exhibited a XP phenotype in accordance with established XP‐causing mutations (c.2079G>A, p.R683Q; c.2078G>T, p.R683W; c.1833G>T, p.R601L; c.1878G>C, p.R616P; c.1878G>A, p.R616Q). One TTD patient was homozygous for the known TTD‐causing mutation p.R722W (c.2195C>T). Two patients were compound heterozygous for a TTD‐causing mutation (c.366G>A, p.R112H) and a novel p.D681H (c.2072G>C) amino acid exchange, but exhibited different TTD and XP/CS complex phenotypes, respectively. Interestingly, the XP/CS patient's cells exhibited a reduced but well detectable XPD protein expression compared with hardly detectable XPD expression of the TTD patient's cells. Same mutations with different clinical outcomes in NER‐defective patients demonstrate the complexity of phenotype–genotype correlations, for example relating to additional genetic variations (parental consanguinity), different allelic expression due to SNPs or differences in the methylation status.